1997
DOI: 10.1079/bjn19970103
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cultural determinants of meal size and frequency

Abstract: Total energy intake and the frequency and size of meals are profoundly influenced by the sociocultural context in which it occurs. Simply eating with one other person increases the average amount ingested in meals by 44% and with more people present the average meal size grows even larger. The impact of social facilitation of energy intake on the individual appears to result from genetic effects both on the individuals' sensitivity to the presence of other people and also on the number of other people an indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
1
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 67 publications
4
77
1
7
Order By: Relevance
“…Studies in both laboratory animals and humans show that external cues associated previously with food (learned cues) exert powerful control over feeding behavior. Learned cues can override regulatory signals linked to energy balance (Weingarten, 1983;De Castro, 1997), and disturbance in the extrinsic control of feeding systems may cause overeating (Rodin, 1981;Wardle, 1988;Booth, 1989). The present findings have defined components of brain circuitry that allow food-associated cues to override "satiety" signals.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Studies in both laboratory animals and humans show that external cues associated previously with food (learned cues) exert powerful control over feeding behavior. Learned cues can override regulatory signals linked to energy balance (Weingarten, 1983;De Castro, 1997), and disturbance in the extrinsic control of feeding systems may cause overeating (Rodin, 1981;Wardle, 1988;Booth, 1989). The present findings have defined components of brain circuitry that allow food-associated cues to override "satiety" signals.…”
Section: Discussionmentioning
confidence: 78%
“…Overeating is attributable, at least in part, to the fact that food consumption is powerfully influenced by a variety of environmental factors that are unrelated to energy requirements (Rodin, 1981;Booth, 1989). Eating can be socially facilitated (De Castro, 1997), and cues that become associated with food when hunger prevails can increase eating in satiated states (Weingarten, 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the total energy and nutrient intakes increase when individuals eat with others [23]. However shift workers have fewer opportunities to take meals with their families and friends.…”
Section: Discussionmentioning
confidence: 99%
“…However, physiology is only one facet of the complex array of effectors of ingestive behaviors of free-living individuals. Recent studies have added to our understanding of the powerful modulating role of environmental cues and social contexts in affecting the amount of food consumed (20,21). Therefore, the likelihood that observed effects of manipulations of a single or limited number of meal characteristics in the laboratory will be replicated in free-living individuals is low.…”
Section: Introductionmentioning
confidence: 99%